Developing instructional materials for problem-solving essay writing through animated video integration - Mariana Ulfah Hoesny; Maya Rizki Fauzia; Isnaini Nur Safitri; Atiqah Nurul Asri (JL3T (Journal of Linguistics, Literature and Language Teaching), 2026)
Writing is a complex skill since it deals with cognitive abilty as well as linguistic skill. Writing process does not only involve transforming ideas into text, but also  undergo some processes such as drafting, writing, and revising. This study is aimed at developing writing learning material of problem solving essay, assisted by animated video. Design and Development research with ADDIE approach was employed. The material is developed to support the teaching of writing problem-solving essay, thus it is started with a text, comprehension question and glossary. The text is a problem-solving text to give students a prior example before starting to write. The material also cover grammar corner which explain language features needed to write problem-solving essay. Additionally, a step-by-step guide to write the essay is presented. Each step is accompanied by exercise to facilitate the writing. Finally an animated video is created to help students understand more about the essay. Methods of data collection employed were interview and questionnaires. Questionnaires were distributed to 30 second grade students of BIKBP study program. The sampling technique was purposive sampling since the participants were selected based on some criteria such as had taken Essay Writing course and at least second grade students. The score gained from content validation was 94 out of 100, in addition media expert validation score 92 out of 100. The result of validation indicated that the instructional material and video can be applied with minor revision. The result of evaluation shows that the learning material and animated video is in ‘good’ category. It was underlined that the duration of video should be longer, however other aspects were considered good and both products can be used to teach problem-solving essay. Thus, it can be concluded that the learning material supported by animated videos for essay writing were helpful for students.